Association of dominant tree species in lowland forest of Mount Ciremai National Park - Yayan Hendrayana; Deni Deni; Ade Muhammad Irsyad Habibi (Mangifera Edu, 2022)
The vegetation of the Karangsari rehabilitation zone of Mount Ciremai National Park vegetation consists of several trees that grow together and interact with each other. This study aimed to determine species diversity and dominant tree associations in the rehabilitation zone of Karangsari Block, Mount Ciremai National Park. Field data collection using the checkered line method on a predetermined number of sampling plots. Furthermore, it was analyzed using the Important Value Index (IVI) to determine the dominant tree species and to determine the association relationship using a 2 x 2 contingency table. The study found 22 tree species with a diversity index value of 1.4. The dominant trees found in the study area were tusam (Pinus merkusii), saninten (Castanopsis argantea), anggrit (Nauclea sp), and avocado (Persea americana). There are six pairs of association relationships between dominant trees four pairs are positive and two are negative. This information is essential for future management of the use zone.